PENGALAMAN PERAWAT DALAM PELAKSANAAN TERAPI AKTIVITAS KELOMPOK - Eva Sinaga; Madya Sulisno (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Psychiatric disorder is a syndrome or psychological or behavioral pattern that occurs in individuals and associated with the presence of distress, disability, significantly increasing risk for death, sickness, disability, or loss of freedom. It may become more serious and should be given any treatment. One of the methods to overcome psychiatric disorder is by group activity therapy as a nursing intervention. The study aimed to find out nurse’s experience in the group activity therapy implementation on patients with psychiatric disorders. Qualitative research with a phenomenological approach, involved nurse who was minimum bachelor degree, had ≥ 5 years of service and had group activity therapy training certificate. Sampling method was purposive sampling with 6 participants. In-depth interview was used as the data collection technique. The results showed that nurse’s experienced positive and negative feelings in the therapy implementation. Some of their obstacles were inadequate infrastructure, the group’s dynamic and inadequate conditions of nurses. According to the situation, nurses made some modifications involving the infrastructure along with human resources modification and patients’ nursing problems combination. Support that was given to nurses in group activity theraphy is covering instrumental support and acknowledgement. Based on the result, to overcome the obstacles, increasing routine monitoring and group activity therapy training need to be considered